TPX2 Impacts Acetylation of Histone H4 at Lysine 16: Implications for DNA Damage Response - Neumayer, Gernot; Nguyen, Minh Dang (PLOS ONE, 2014)
During interphase, the spindle assembly factor TPX2 is compartmentalized in the nucleus where its roles remain largely uncharacterized. Recently, we found that TPX2 regulates the levels of serine 139-phosphoryated H2AX (γ-H2AX) at chromosomal breaks induced by ionizing radiation. Here, we report that TPX2 readily associates with the chromatin in the absence of ionizing radiation. Overexpression of TPX2 alters the DAPI staining pattern of interphase cells and depletion of TPX2 constitutively decreases the levels of histone H4 acetylated at lysine16 (H4K16ac) during G1-phase. Upon ionizing irradiation, this constitutive TPX2 depletion-dependent decrease in H4K16ac levels correlates with increased levels of γ-H2AX. The inversely correlated levels of H4K16ac and γ-H2AX can also be modified by altering the levels of SIRT1, herein identified as a novel protein complex partner of TPX2. Furthermore, we find that TPX2 depletion also interferes with formation of 53BP1 ionizing radiation-induced foci, known to depend on γ-H2AX and the acetylation status of H4K16. In brief, our study is the first indication of a constitutive control of TPX2 on H4K16ac levels, with potential implications for DNA damage response.